2016
DOI: 10.1002/acr.22800
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin G Levels as a Prognostic Factor for Autoimmune Hepatitis Combined With Systemic Lupus Erythematosus

Abstract: Objective. Autoimmune hepatitis (AIH) is a chronic progressive liver disease characterized by circulating autoantibodies and hyperglobulinemia. This study was conducted to identify the features of AIH accompanied by systemic lupus erythematosus (SLE-AIH) that differ from those of primary AIH (P-AIH), and to evaluate factors that affect the outcome for SLE-AIH patients. Methods. From May 1995 to April 2014, clinical data (including liver pathology) from 164 patients with P-AIH and 23 patients with SLE-AIH were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 36 publications
2
16
0
Order By: Relevance
“…Elevated level of serum IgG is a poor prognostic factor for autoimmune hepatitis associated with SLE. Additionally, the deposition of IgG is reported to cause tissue damage [24,25]. The serum IgG levels correlated with the serologic activity and can predict disease ares in patients with LN.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated level of serum IgG is a poor prognostic factor for autoimmune hepatitis associated with SLE. Additionally, the deposition of IgG is reported to cause tissue damage [24,25]. The serum IgG levels correlated with the serologic activity and can predict disease ares in patients with LN.…”
Section: Discussionmentioning
confidence: 99%
“…Although SLE affects various organ systems, liver involvement is usually not part of the disease spectrum [3,4]. The reasons of deranged liver enzymes in SLE patients are hepatotoxic drugs, viral hepatitis, fatty liver disease associated with steroid use and less commonly primary liver disease, hepatic congestion or lupus hepatitis [2]. It is quite rare to find an autoimmune hepatitis and SLE overlap and is usually considered when patients fulfill the American College of Rheumatology criteria for systemic lupus erythematous and International autoimmune hepatitis group scoring for AIH [5].…”
Section: Discussionmentioning
confidence: 99%
“…Doo Ho Lim et al showed that patients with SLE -AIH overlap and have much higher levels of IgG than those with primary autoimmune hepatitis and that those with SLE -AIH patients who had cirrhosis had higher levels of IgG than those without cirrhosis. They also noticed that the serum IgG levels normalized in patients with SLE-AIH without cirrhosis after treatment suggesting that IgG can be used as a marker for prognosis in SLE-AIH [2].…”
Section: Distinguishingmentioning
confidence: 94%
See 1 more Smart Citation
“…The level of serum IgG is also a valuable predictor for the risk of infection in transplant recipients [8][9][10]. Moreover, high IgG levels are indicators of autoimmunity (e.g., demyelinating diseases, lupus erythematosus), chronic infection, liver diseases (e.g., autoimmune hepatitis), and lymphoproliferative disorders (e.g., multiple myeloma) [3,[11][12][13][14]. The early diagnosis of these conditions is a key factor to minimize the risk of permanent organ damage and to proceed with adequate therapy, accounting for less morbidity and mortality [14,15].…”
Section: Introductionmentioning
confidence: 99%